Physical-chemical characterization of water from an amazon urban river, Capanema, Pará, Brazil (Research, Society and Development, 2021)
The occupation of the banks of urban rivers impacts aquatic environments through the release of effluents and residues, removal of riparian vegetation and changes in the configuration of rivers. With this, this work aimed to carry out the physical-chemical characterization of the Ouricuri river in Capanema, considering the spring area, urban perimeter and mouth, observing the influence of seasonality and urban growth. Temperature (T), pH, dissolved Oxygen (DO) and electrical conductivity (EC) were evaluated. The temperature was higher in the urban area (27.81ºC) in the less rainy season (EMC) and 29.26ºC in the rainy season (EC), influenced by the removal of riparian vegetation. The spring area showed acid pH (N1 = 4.91 and 4.27 in EMC and EC), influenced by the lentic character of the collection points and the contribution of organic matter, the pH was basic in the urban area due to the concentration of domestic effluents in the river. The content of DO was higher in the spring region, (N3 = 3.10 mg/L in EMC and 4.92 mg/L in EC), the parameter decreased in urban areas and mouth, influenced by temperature and decomposition of matter organic. The spring had the lowest EC (N1 = 12.7 µS cm-¹ and 25.3 µS cm-¹ for EMC and EC), and the mouth of the highest levels, EC is influenced by the input of untreated effluents. It was found that the occupation of the banks of the Ouricuri river harms the urban aquatic environment, through changes in the physical environment, which alter the physicochemical variables indicative of water quality.